RECONSTRUCTION OF THE LEGISLATION HIERARCHY IN LAW 12 YEAR 2011 BASED ON THE VALUES OF PANCASILA JUSTICE - Isnawati Isnawati (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2022)
The hierarchy of laws and regulations in Indonesia is regulated in Law Number 12 of 2011 concerning the Establishment of Legislations, in principle lower regulations may not conflict with higher regulations. However, in Law Number 12 of 2011 concerning the Formation of Legislations, there are weaknesses, which have implications for the implementation of laws and regulations in Indonesia. This study uses a normative juridical approach, using a statute approach and a case approach. The finding in this article is that the reconstruction of the hierarchy of laws and regulations needs to be done by placing Pancasila as the highest basic norm, which can become the truth in the entire legal system in Indonesia.